2005
DOI: 10.1007/bf02344720
|View full text |Cite
|
Sign up to set email alerts
|

Position-sensing technologies for movement analysis in stroke rehabilitation

Abstract: Research has focused on improvement of the quality of life of stroke patients. Gait detection, kinematics and kinetics analysis, home-based rehabilitation and telerehabilitation are the areas where there has been increasing research interest. The paper reviews position-sensing technologies and their application for human movement tracking and stroke rehabilitation. The review suggests that it is feasible to build a home-based telerehabilitation system for sensing and tracking the motion of stroke patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(86 citation statements)
references
References 67 publications
2
80
0
1
Order By: Relevance
“…This 2.2°error does not exceed the 5°mean error limit established by the American Medical Association for reliable evaluation of movement impairments in a clinical context and is therefore clinically insignificant. 24 Furthermore, the fast Fourier transform analysis revealed that the iPhone app and dynamometer recorded the same dominant frequencies during rotation of the dynamometer's movement arm. Finally, the iPhone app demonstrated a high level of precision, with the coefficients of variation measuring less than 3% for all speeds except 150°/s (6.8%).…”
Section: Discussionmentioning
confidence: 96%
“…This 2.2°error does not exceed the 5°mean error limit established by the American Medical Association for reliable evaluation of movement impairments in a clinical context and is therefore clinically insignificant. 24 Furthermore, the fast Fourier transform analysis revealed that the iPhone app and dynamometer recorded the same dominant frequencies during rotation of the dynamometer's movement arm. Finally, the iPhone app demonstrated a high level of precision, with the coefficients of variation measuring less than 3% for all speeds except 150°/s (6.8%).…”
Section: Discussionmentioning
confidence: 96%
“…In particular, in 5-10 years, the gaming scenario will probably be dominated by games where the user will interactively control virtual characters by using some easily wearable devices (at most 4-5 on the whole body, e.g., possible locations could include feet, ankles, wrists, and head [15,17,33]). The medical scenario will instead begin to adopt wearable sensors able to assess health of the patients by remotely measuring vital signs/parameters and allowing patients to freely stay at their homes still keeping a direct connection with their doctors [5,7,18,23,24,25,29,37,38,41,42].…”
Section: Future Directionsmentioning
confidence: 99%
“…This is also reflected by various efforts already spent in developing mHealth applications based, for instance, on the use of inertial sensors [5,23,24,25,37,41].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, there are now novel sensors and mobile devices that can be used to measure and monitor a variety of human activities in the home -for example, for the detection of the number of steps taken, the detection of sitting and standing postures, or the precise angle between the upper and lower arm of a person stretching their arm [3,4,9]. There is much potential for using these versatile and lightweight technologies in the development of augmented rehabilitation therapy for people with stroke [10].…”
Section: Potential Of Novel Technologiesmentioning
confidence: 99%